A case study of inter-examiner feedback from a UK context: Mixing research methods to gain insights into situated learning interactions - Johnson, Martin (Formation et pratiques d’enseignement en question, 2014)
This research project explores professional senior examiners’ emerging practices when feeding back to examiners under their supervision in a new technological environment. Activity theory is used to explore feedback communication mode choices. Three methods are used; video observation with stimulated recall interviews, surveys of practice, and telephone interviews. Research outcomes highlight the complexities of senior examiner decision-making, showing how the affordances of communication mode at times influence choices around how to feedback. The outcomes also show that inter-subjective concerns also have an influence on senior examiners’ feedback communication mode choices.